Traditional techniques in management of stored grain pests from Goa - Shelke, R T; Kulkarni, Rajender Rao; Kawale, R R (Journal of Postharvest Technology, 2021)
Post-harvest losses of food grains are due to unscientific storage, insects, rodents, micro- organisms etc. (Ministry of Consumer Affairs, Food & Public Distribution). In Goa, though the Production is less the food grains are stored for home consumption throughout the year. The climatic condition of Goa is hot and humid which is favourable f or the incidence of several stored grain pests. Major stored grain pests observed in Goa are Rice weevil, Rice moth in cereals i.e. in paddy and nagali, Pulse beetle in cowpea and other stored pulses, Red rust flour beetle in flour or suji. The increasing public awareness of the environmental contamination by toxic chemical residues has necessitated the research and development of non-chemical methods of pest management. Traditional agricultural practices have profound effect on modern day agriculture. So, this research aimed to find out traditional techniques used by Goan farmers for Post-harvest Storage. Farmers have developed various storage stuctures viz., Mudi, Vurlo, Kado, kadtari etc., used for safer storage of Agricultural produce. Various traditional techniques including some plant products, ash used by local farmers as an additive for prolonged storage of seed grain were explored.